The Effect of Ribs on Behavior of Natural Gas Vehicle Platform Backbone with Stamping Consideration - Sahari, Barkawi; Arsad, N. M.; Hamouda, Abdel Magid Salem; Wong, Shaw Voon; Ahmad, M. F. (2008)
The platform is the basic automotive body structure. It is on this platform that engine and other components are attached. It is made by stamping of sheet metal. The main parts are the front and rear. Backbone made of stronger material is used to strengthen the platform. It is located in the central portion of the platform. For natural gas vehicle, a gas tank is placed underneath the backbone. The backbone is designed for high stiffness and ribs are used. The ribs may cause tearing during stamping. The objective of this paper is to determine the number of ribs that give high stiffness of the backbone without causing defect during stamping. Finite element is used. The backbone with 3, 4 and 5 ribs was investigated. It was found that backbone with 3 ribs is sufficient for no failure during stamping. Backbone with 5 ribs shows through thickness crack during stamping.